The Capital Adequacy, Asset Quality, Management Quality, Earning Quality, and Liquidity Analysis in Indonesia Banking Sectors - Marta Elviani; Alfonsa Dian Sumarna (Jurnal Akuntansi, 2024)
Risks likely to arise and hinder profitability can be measured using the CAMELanalysis conducted in this study. CAMEL and profitability are fundamentalaspects that are highlighted to determine the financial performance of banksectors. It can be said that if the profitability value of a business is good, itreflects good financial performance. Increased profitability is the success ofmanagement in managing the risks detected. The specific purpose of this studyis to measure each proxy that represents CAMEL analysis on the profitabilityvalue conveyed by the average return on equity (ROAA) variable in the bankingsector so that bank management can manage risk well and generate highprofits. This research was conducted using quantitative methods and secondarydata in the form of databases, namely company financial report documents andcompany annual reports downloaded through the official website of theIndonesia Stock Exchange and processed using Eviews software. Conventionalbanks listed on the Indonesia Stock Exchange for the period 2020-2022, asmany as 41 banks became the sample of this study. The results showed thatCAR, NPL, BS, and LDR had a significant effect on banking profitability, whileNIM had no significant effect on banking profitability